2016
DOI: 10.1007/s10143-016-0801-0
|View full text |Cite
|
Sign up to set email alerts
|

Can MRI predict meningioma consistency?: a correlation with tumor pathology and systematic review

Abstract: Tumor consistency is a critical factor that influences operative strategy and patient counseling. Magnetic resonance imaging (MRI) describes the concentration of water within living tissues and as such, is hypothesized to predict aspects of their biomechanical behavior. In meningiomas, MRI signal intensity has been used to predict the consistency of the tumor and its histopathological subtype, though its predictive capacity is debated in the literature. We performed a systematic review of the PubMed database s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 35 publications
(88 reference statements)
1
56
1
10
Order By: Relevance
“…14,15 The TCTI ratio offers a simple way to normalize the T2W intensity, has been extensively characterized in meningiomas, and has shown to strongly correlate with tumor consistency. [9][10][11] The use of this ratio in pituitary adenomas has offered promising results in a small cohort. 12 Using a large cohort, we show that the TCTI ratio does not correlate well with tumor consistency and does not offer predictive value in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 The TCTI ratio offers a simple way to normalize the T2W intensity, has been extensively characterized in meningiomas, and has shown to strongly correlate with tumor consistency. [9][10][11] The use of this ratio in pituitary adenomas has offered promising results in a small cohort. 12 Using a large cohort, we show that the TCTI ratio does not correlate well with tumor consistency and does not offer predictive value in this context.…”
Section: Discussionmentioning
confidence: 99%
“…TCTI ratio strongly correlates with tumor consistency, and TCTI ratios >1.8 correlate with softer tumors. [9][10][11] A recent study demonstrated that the use of the ratio of signal intensity of pituitary adenoma to cerebellar peduncle on T2W imaging (TCTI) correlates well with tumor consistency, and all six firm tumors in their series had a TCTI <1.8. 12 We therefore sought to validate these results in a larger patient cohort.…”
Section: Introductionmentioning
confidence: 99%
“…MRI is the key method for diagnosis and characterisation of meningiomas, resection planning, therapy decisions and monitoring of therapy [5,7,10]. Typical meningiomas occur sessile or lentiform in shape and are sharply circumscribed showing wide dural attachments.…”
Section: Introductionmentioning
confidence: 99%
“…It is also relevant to mention that a prior meta-analysis regarding meningiomas and predicting consistency based on imaging found that all studies that relied on quantitative assessment of tumor signal intensity found a correlation between intensity and consistency for these tumors. 22 The only studies that did not find a correlation for this pathology were those that used a qualitative assessment. 22 It seems likely that a similar trend would be true with VSs, which could explain why the study by Rizk et al did not find the strong correlation identified by the Copeland et al 17,18 These aforementioned studies additionally identified a trend toward and correlation between consistency and CN VII outcomes, at least initially in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…18 Preoperative neuroimaging as a predictor of internal tumor consistency, a concept that is utilized frequently with other benign brain tumors, is incompletely understood for VSs. [19][20][21][22] Copeland et al determined that T2-weighted magnetic resonance imaging (MRI) protocols can be utilized to determine consistency of VSs, with hyperintensity signifying a softer tumor. 17 Contrarily, Rizk et al found that T2 intensity did not correlate with consistency of the tumor intraoperatively, while widening of the internal auditory canal (IAC) on computed tomography (CT) imaging did correlate with firm tumors significantly widening the IAC compared with soft tumors.…”
Section: Introductionmentioning
confidence: 99%